Comparative analysis of gene expression in tea plant (Camellia sinensis (L.) Kuntze) under low-temperature stress - L. S. Samarina; A. O. Matskiv; N. G. Koninskaya; T. A. Simonyan; V. I. Malyarovskaya; L. S. Malyukova (Вавиловский журнал генетики и селекции)
Low-temperature stress is one of the main factors limiting the distribution and reducing the yield of many subtropical crops, including the tea crop. Efficient breeding to develop frost-tolerant cultivars requires a reliable set of genetic markers for identifying resistance donors, and that is why it is necessary to reveal the specific genetic response in frost-tolerant genotypes in comparison with frost- susceptible ones. In this work, we performed a comparative analysis of the expression of 18 tea genes (ICE1, CBF1, DHN1, DHN2, DHN3, NAC17, NAC26, NAC30, bHLH7, bHLH43, P5CS, WRKY2, LOX1, LOX6, LOX7, SnRK1.1, SnRK1.2, SnRK1.3) under cold and frost conditions in two tea genotypes, tolerant and susceptible. Low-temperature stress was induced by placing the potted plants in cold chambers and lowering the temperature to 0…+2 °С for 7 days (cold stress), followed by a decrease in temperature to –4…–6 °С for 5 days (frost stress). Relative electrical conductivity of leaf was measured in response to the stress treatments, and a significant difference in the frost tolerance of the two tea genotypes was confirmed. Cold exposure did not lead to a change in the electrical conductivity of leaf tissue. On the other hand, frost treatment resulted in increased REC in both genotypes and to a greater extent in the susceptible genotype. Increased expression of all the genes was shown during cold and frost. The genes that were strongly expressed in the tolerant tea genotype were revealed: ICE1, CBF1, DHN2, NAC17, NAC26, bHLH43, WRKY2, P5CS, LOX6, SnRK1.1, SnRK1.3. These genes can be proposed as markers for the selection of frost-tolerance donors in tea germplasm collections. Additionally, it was shown that the tolerant genotype is characterized by an earlier response to stress at the stage of cold acclimation. The study of the expression of the identified genes in different organs of tea plants and in different exposures to low temperature is relevant for further investigations.